FGF1 and FGF2 mutations in preeclampsia and related features. (July 2016) - Marwa, Ben Ali Gannoun; Raguema, Nozha; Zitouni, Hedia; Feten, Hachani Ben Ali; Olfa, Kacem; Elfeleh, Raja; Almawi, Wassim; Mahjoub, Touhami
Abstract: Background: Fibroblast growth factor ( FGF ) 1 and FGF 2 were previously linked with preeclampsia (PE), possibly through altering decidual and placental FGFR2 expression. Since common variation in FGF1 and FGF2 might influence FGF1 and FGF2 activity, this study evaluated whether common FGF1 and FGF2 variants are linked with PE and associated features. Methods: The association between FGF1 rs34011 and FGF2 rs2922979 SNPs and PE were tested in 300 women with PE, and 300 age-matched control women. Results: The allelic distribution of FGF1 rs34011 ( P  < 0.001) but not FGF2 rs2922979, variants were significantly different between PE cases and control women. Marginal association of FGF2 rs2922979 was seen after controlling for key covariates. Setting homozygous major allele genotype (1/1) as reference, significantly higher frequencies of heterozygous rs345011, and reduced frequency of heterozygous rs2922979 genotype carriers were seen in PE cases; the distribution of the remaining genotypes were comparable between cases and controls. Carriage of rs2922979 minor allele correlated with fasting glucose ( P  = 0.02), while the presence of rs34011 minor allele was not correlated with PE-associated features. Conclusions: Our study suggests that the genetic variants of FGF1 rs34011, more so than FGF2 rs2922979, may play a role in PE pathogenesis in Tunisian women. These findings need confirmation in other ethnic populations. Highlights: We genotyped 2 SNPs in FGF1 and FGF2 genes in Tunisian women with preeclampsia (PE). FGF1 rs3401, but not FGF2 rs2922979, variants were significantly associated with PE. Marginal association of FGF2 rs2922979 was seen after controlling for key covariates. Carriage of rs2922979 minor allele correlated with fasting glucose.